Transhepatic antegrade embolization of the esophageal and gastric varices with Onyx® - Barbaros Erhan Çil; Ferdi Çay; Bora Peynircioğlu; Ege Altan; Taylan Kav (Turkish Journal of Gastroenterology, 2019)
-